Republic of Azerbaijan : 2010 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Azerbaijan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper presents the key findings of the Republic of Azerbaijan's 2010 Article IV Consultation. In 2009, overall GDP grew at 9.3 percent, but non-oil GDP growth slowed from 16 percent to 3 percent, fiscal and export revenues fell by more than 30 percent, and credit and liquidity conditions tightened substantially. Owing to the authorities' appropriate policy response, the exchange rate remained stable, inflation dropped dramatically, official poverty rates continued to fall, and financial stability was maintained.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet